Strength-based material layout optimization of solid reinforced concrete. (February 2023) - Andersen, Mads Emil Møller; Poulsen, Peter Noe; Olesen, John Forbes; Hoang, Linh Cao
Highlights: Strength-based structural/material layout optimization for solid reinforced concrete. The design cost is minimized based on the individual price of concrete and reinforcement. The optimization is strength-based, i.e., strength scaling parameters on the concrete and reinforcement ratios are used. The material layout is defined based on the concrete strength scaling parameters and reinforcement ratios. Abstract: Whether monetary, environmental, or otherwise, the cost of the structure is always an important aspect when designing reinforced concrete. A structure with a low cost is desirable, but other considerations must be made. First and foremost, the structures should be safe. The two conditions define the structural optimization problem that this paper seeks to solve as finding the structure with the lowest cost, which is also safe. Validation of reinforced concrete in the ultimate limit state is often performed using plasticity and strength-based methods. This paper combines Finite Element Limit Analysis (FELA) with a yield criterion that includes material layout variables to create a strength-based structural optimization framework for solid reinforced concrete structures. The yield criterion combines the Modified Mohr–Coulomb criterion, where variables scale the compressive strength, with the inclusion of smeared reinforcement, where variables scale the reinforcement ratios. The framework is presented and shown in examples using free optimization and examples where material layout variables in parts of the structure are coupled and optimized as a group.